Medium Access Control in WSN Network for water management system - Bahallah, Meriem; Djir, Takwa; Oulad Djedid, Lakhdar Kamel, Directeur de thèse (Laghouat : Université Amar Telidji - Département d'informatique, 2024)
Nowadays, wireless sensor networks (WSNs) are widely used for collecting and disseminating data from sensor nodes to centralized systems. In this context, a corporation like the Algerian Water Corporation (ADE), which relies on manual methods, faces significant limitations, including inefficiency and the inability to promptly detect and respond to issues. Through the employment of different sensors and transmission modules, WSNs enhance water management activities, including the quality and quantity of water. Despite these benefits, WSNs face problems such as network congestion and the critical need for effective Medium Access Control (MAC) protocols. These protocols are important for maintaining the efficiency of the network, controlling collisions, and prolonging the network’s operational lifespan. WSNs have several nodes that produce different data with different transmission rates and urgency, hence creating congestion and unnecessarily high collisions. An effective (MAC) protocol provides equal access to the channel and improves energy consumption as well as throughput. To address these problems, therefore, this dissertation proposes a new (MAC) protocol. The performance of the proposed protocol is analyzed thoroughly and extensively through simulation using the NS2 simulator. The protocol demonstrates higher performance in terms of reducing collisions, improving scalability, and achieving higher throughput compared to existing protocols. Hence, this work provides a significant improvement in WSN communication protocols because it presents a reliable solution for water management systems; at the same time, it establishes a basis for future research in the field.